2007
DOI: 10.1038/sj.gene.6364378
|View full text |Cite
|
Sign up to set email alerts
|

CCL3L1 and CCL4L1: variable gene copy number in adolescents with and without human immunodeficiency virus type 1 (HIV-1) infection

Abstract: As members of the chemokine family, macrophage inflammatory protein 1 alpha (MIP-1a) and MIP-1b are unique in that they both consist of non-allelic isoforms encoded by different genes, namely chemokine (C-C motif) ligand 3 (CCL3), CCL4, CCL3-like 1 (CCL3L1) and CCL4L1. The products of these genes and of CCL5 (encoding RANTES, i.e., regulated on activation, normal T expressed and secreted) can block or interfere with human immunodeficiency virus type 1 (HIV-1) infection through competitive binding to chemokine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
36
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 55 publications
(72 reference statements)
5
36
0
Order By: Relevance
“…For example, some reports demonstrated an association between high CCL3L1 copy numbers and a reduced prevalence of HIV seropositivity, slower progression to AIDS, and improved recovery of CD4 ϩ T cells (45,(56)(57)(58), whereas other studies and follow-up correspondences failed to detect an association even within the same data set (59)(60)(61). Some researchers have suggested that the CCL3L1 copy number estimation method used in those association studies could be flawed, for example, due to DNA degradation, inconsistent quality among DNA samples, the use of inappropriate DNA amounts in the real-time PCR assay, inappropriate comparison of threshold cycle (C T ) values from samples run in different real-time PCR experimental repeats, or inappropriate rounding of copy numbers to the nearest integer value.…”
Section: Discussionmentioning
confidence: 96%
“…For example, some reports demonstrated an association between high CCL3L1 copy numbers and a reduced prevalence of HIV seropositivity, slower progression to AIDS, and improved recovery of CD4 ϩ T cells (45,(56)(57)(58), whereas other studies and follow-up correspondences failed to detect an association even within the same data set (59)(60)(61). Some researchers have suggested that the CCL3L1 copy number estimation method used in those association studies could be flawed, for example, due to DNA degradation, inconsistent quality among DNA samples, the use of inappropriate DNA amounts in the real-time PCR assay, inappropriate comparison of threshold cycle (C T ) values from samples run in different real-time PCR experimental repeats, or inappropriate rounding of copy numbers to the nearest integer value.…”
Section: Discussionmentioning
confidence: 96%
“…This is significant because copy number of both genes can be different on a single chromosome. 14,25 However, the number of copies of CCL3L and CCL4L is, in general, positively correlated within populations. Thus, although in this study, we focused on the therapeutic correlates of CCL4L gene copy number, CCL3L gene dosage may also contribute to the LT rejection effect.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of genomic copy number varition of Asian men with congenital bilateral absence of the vas deferens (CBAVD) but without the most common CFTR-associated mutant did identify CNV in genes possibly associated with the disorder [Lee et al 2009]. Initial studies of CNVs have shown associations in complex disorders such as systemic lupus, HIV acquisition, and breast cancer [Yang et al 2007;Shao et al 2007;Frank et al 2007].…”
Section: Discussionmentioning
confidence: 99%